LDL-cholesterol: standards of treatment 2016 : a German perspective - März, Winfried; Grammer, Tanja B. (American journal of cardiovascular drugs, 2016)
Decreasing low-density lipoprotein cholesterol (LDL-C) is one of the few established and proven principles for the prevention and treatment of atherosclerosis. The higher the individual cardiovascular risk, the higher the benefit of lipid-lowering pharmacotherapy. Therefore, treatment options are chosen based on a patient’s total cardiovascular risk. The latter depends not only on the levels of LDL-C but also on the presence of cardiovascular disease (CVD) and on the number and severity of other risk factors. Current guidelines recommend the lowering of LDL-C to 115 mg/dl (3 mmol/l) in patients with low and moderate risk. The LDL-C treatment target is <100 mg/dl (2.6 mmol/l) for patients at high risk and <70 mg/dl (1.8 mmol/l) for patients at very high risk. Although lifestyle measures remain a fundamental part of treatment, many patients require drug therapy to achieve their LDL-C targets. Statins are the drugs of choice, with other options including ezetimibe and the newly available monoclonal antibodies against PCSK9 (proprotein convertase subtilisin/kexin type 9). In some cases, bile acid-binding sequestrants and fibrates can also be considered. Nicotinic acid is no longer available in Germany. PCSK9 antibodies decrease LDL-C about 50-60 % and are well tolerated. Their effects on clinical endpoints are being investigated in large randomized trials. The aim of the present review is to summarize the current guidelines and treatment options for hypercholesterolemia. Moreover, we provide an appraisal of PCSK9 antibodies and propose their use in selected patient populations, particularly in those at very high cardiovascular risk whose LDL-C levels under maximally tolerated lipid-lowering therapy are significantly over their treatment target.